فاعلية برنامج إرشادي باستخدام اللعب في خفض حدة التنمر وتحسين مستوى بعض المهارات الاجتماعية لدى عينة من الأطفال - عبدالله، الشيماء محمود محمد; بهادر، سعدية محمد علي; الشوربجي، عمر السيد عمر (جامعة عين شمس - كلية الدراسات العليا للطفولة, 2023)
الهدف: التحقق من فاعلية برنامج إرشادي باللعب في خفض حدة التنمر وتحسين أهم المهارات الاجتماعية لدى عينة من أطفال المرحلة الابتدائية البالغين من العمر من (٦ -٩) سنوات. المنهج: استخدمت هذه الدراسة المنهج التجريبي. الأدوات: استمارة البينات الأولية، مقياس المتنمر عليهم، مقياس المهارات الاجتماعية. العينة: تكونت عينة الدراسة من ۳۰ طفلا وطفلة (15 ذكور، ١٥ إناث) تم اختيار العينة بالطريقة العمدية. النتائج: توجد فروق إحصائية دالة بين متوسطات درجات أفراد عينة الدراسة على مقياس التنمر والمهارات الاجتماعية (قبل/ بعد) تطبيق برنامج الإرشاد باللعب لصالح التطبيق البعدي عند مستوى دالة 0.05. لا توجد فروق دالة إحصائية بين متوسطات درجات أفراد عينة الدراسة على مقياس التنمر والمهارات الاجتماعية بعد مضي شهر من تطبيق برنامج الإرشاد باللعب وعند مستوى دالة 0.05. Objective: Verifying the effectiveness of a counseling program of playing in reducing the severity of bullying and improving the most important social skills among a sample of primary school children aged (6- 9) years. Methodology: The study included 30 children, aged from (6 to 9) years. For each the following were done: Scale of Bullying Behavior (by researcher), Scale of Social Skills (by researcher) & A Counseling Program for Reducing Severity of bullying and improving some Social Skills (by researcher). Results: There are statistically significant differences between the mean grades of individuals on date scale and social skills (before/ after) apply counseling program by playing for the dimensional application at a function level. There are statistically significant differences between the mean scores of the study sample members (females/ males) on the Social Skills scale for application for a female sample at a function level. There are statistical differences are significant between the averages bullying and social skills after a month of the program with a return level function.
Keywords: البرامج الإرشادية -- ظاهرة التنمر -- التنمر المدرسي -- المهارات الاجتماعية -- طلبة المدارس